Epidemiology of unintentional drowning in a metropolis of the French Mediterranean coast: a retrospective analysis (2000–2011). Issue 3 (2nd July 2016) - Bessereau, Jacques; Fournier, Nathalie; Mokhtari, Tarik; Brun, Pierre-Marie; Desplantes, Agnalys; Grassineau, Dominique; Guilhem, Noël; Heireche, Fouzia; Kerbaul, François; Mancini, Julien; Meyran, Daniel; Toesca, Richard; et al.
Abstract : Drowning affects more than 500, 000 people worldwide and is responsible for at least 350, 000 deaths each year. In France, 1235 drowning resulting in 496 deaths were recorded in the summer 2012. This retrospective study has investigated the epidemiology of drowning in the city of Marseille (South of France) between 2000 and 2011. We identified 449 cases of unintentional drowning. The highest incidence was found among males with a median age of 36 years. The incidence was 5.3 victims per 10, 000 inhabitants with a mortality rate of 1.2 per 10, 000. These accidents occurred mainly at sea (89%) and during the summer season. A majority of drowning victims (69%) were admitted in a hospital. This is the only study in France to analyse data on drowning throughout the year and over a long period. Drowning is a serious condition burdened by 22% of victims who die.